2017
DOI: 10.1038/s41467-017-01774-z
|View full text |Cite
|
Sign up to set email alerts
|

Implications of improved representations of plant respiration in a changing climate

Abstract: Land-atmosphere exchanges influence atmospheric CO2. Emphasis has been on describing photosynthetic CO2 uptake, but less on respiration losses. New global datasets describe upper canopy dark respiration (R d) and temperature dependencies. This allows characterisation of baseline R d, instantaneous temperature responses and longer-term thermal acclimation effects. Here we show the global implications of these parameterisations with a global gridded land model. This model aggregates R d to whole-plant respiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
110
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 65 publications
0
110
0
Order By: Relevance
“…Stem respiration (R S ) holds a significant role in tree C balances with stem CO 2 efflux to the atmosphere (E A ) being 11% and 20% of global forest ecosystem gross primary production and net primary production, respectively (Yang, He, Aubrey, Zhuang, & Teskey, ). However, relative to photosynthetic CO 2 assimilation, respiratory processes are less understood (Huntingford et al, ; Smith, ), particularly in woody tissues, wherein methodological constraints hinder both quantification of respiratory rates at the organ level (Salomón, Rodríguez‐Calcerrada, & Staudt, ; Teskey, McGuire, Bloemen, Aubrey, & Steppe, ) and scaling up to larger spatial levels (Meir et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Stem respiration (R S ) holds a significant role in tree C balances with stem CO 2 efflux to the atmosphere (E A ) being 11% and 20% of global forest ecosystem gross primary production and net primary production, respectively (Yang, He, Aubrey, Zhuang, & Teskey, ). However, relative to photosynthetic CO 2 assimilation, respiratory processes are less understood (Huntingford et al, ; Smith, ), particularly in woody tissues, wherein methodological constraints hinder both quantification of respiratory rates at the organ level (Salomón, Rodríguez‐Calcerrada, & Staudt, ; Teskey, McGuire, Bloemen, Aubrey, & Steppe, ) and scaling up to larger spatial levels (Meir et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Because of thermal acclimation, predictions of respiration through time based solely on fixed short‐term temperature response functions are rendered invalid, typically resulting in overestimation of respiration in warmer seasons and locations and underestimation in cooler seasons and places (Figure ). Global land surface models that omit foliar temperature acclimation are likely to overestimate the temperature sensitivity of terrestrial carbon exchange (Smith et al, ); however, when aggregated across the globe, respiratory carbon losses were found to be 30% higher than prior estimates (Huntingford et al, ). But the consequences of root respiratory temperature acclimation are not known.…”
Section: Response Of Respiration To Temperature At Multiple Scalesmentioning
confidence: 99%
“…Respiratory metabolism is a fundamental process in plants, providing energy and carbon (C) skeletons needed for growth, survival and agricultural production. In addition, respiratory gas consumption and production by plants also play a crucial role in regulating the chemistry of the atmosphere, and associated rates of global warming (Huntingford et al ., ). Understanding the variation in plant respiratory rate stemming from genetic, developmental and environmental factors provides an opportunity for more predictive modelling of C flows both within plants and between terrestrial land surfaces and the atmosphere (Atkin et al ., ; Tcherkez et al ., ).…”
Section: Introductionmentioning
confidence: 97%